1989
DOI: 10.1109/61.35628
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude comparator based algorithm for directional comparison protection of transmission lines

Abstract: A high speed directional comparison relay based on the evaluation of the locally measured deviations of the voltage and the phase shifted current from their prefault values is described in this paper. The operation of the relay depends on the power frequency components of the voltage and phase shifted current deviation signals. The direction to a fault is determined by an amplitude comparator technique which compares a discriminant value with a positive or negative threshold. Simulation studies on a three-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In a previous research, a DR algorithm based on polarities of VSC and CSC was proposed. In this paper, it is shown that signs of polarities of VSC and CSC are similar for backward faults and contrary for forward faults.…”
Section: Analysis Of the Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous research, a DR algorithm based on polarities of VSC and CSC was proposed. In this paper, it is shown that signs of polarities of VSC and CSC are similar for backward faults and contrary for forward faults.…”
Section: Analysis Of the Simulation Resultsmentioning
confidence: 99%
“…In a previous study, a DRs algorithm has been found on high‐frequency signals of three phase currents and voltages. According to this algorithm, upon fault occurrence is detected, wavelet transform of currents and voltages are calculated.…”
Section: Analysis Of the Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10-13,36,]), voltage dips (e.g. [17,19,22,25,26,[29][30][31]37,39]), occasionally also asymmetry. With the deregulation of power industry, utilities have become increasingly interested in quantifying the responsibilities for power quality problems.…”
Section: Introductionmentioning
confidence: 99%